Sound Wave Teaching Module using STEM-PBL to Improve Students' Science Process Skills - Khadijah, Siti; Suyidno, Suyidno; Mahtari, Saiyidah; Qamariah, Qamariah (Universitas Lambung Mangkurat, 2025)
Students' science process skills are still relatively low because the availability of learning resources such as teaching modules has not improved students' science process skills. Therefore, this study aims to analyze the feasibility of the STEM-PBL-oriented sound wave module to improve students' science process skills. This study uses the ADDIE model, which includes (1) analysis, (2) design, (3) development, and (4) implementation. The trial in this study used a one-group pre-test post-test design on 31 students at one of the state high schools in Banjarmasin City. Data collection was carried out through the validity and practicality of the module, which includes the teaching module and the implementation of the teaching module. The study results for the teaching module's validity value were (3.70 and 0.90) and the practicality value of the teaching module's implementation (was 3.36 and 0.68). Thus, the developed STEM-PBL-oriented sound wave teaching module can be implemented to improve students' science process skills, as seen from its high validity and practicality.